ririn Evaluasi Kebijakan Penguatan Pendidikan Karakter Religiusitas Model Stake di SMKN 1 Duduksampeyan - Ririn Chotimah; Mufarrihul Hazin; Karwanto Karwanto; Amrozi Khamidi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to evaluate the implementation of the policy of strengthening religious character education at SMKN 1 Duduksampeyan. Religious character education is one of the main priorities in forming students who are not only academically competent but also have moral and spiritual integrity. The research method used is a qualitative approach with the STAKE evaluation model which includes the dimensions of antecedent, transaction, and outcomes. The results of the study indicate that this policy has succeeded in increasing students' religious awareness, especially in the discipline of worship, although participation in extracurricular activities based on religion is still low. The conclusion is that although the policy has been effective, additional strategies are needed to increase student participation in non-academic activities so that the impact of religiosity can be more significant. Keywords: Policy Evaluation, Character Education, Religiosity, SMK, STAKE Model